2021
DOI: 10.1089/soro.2019.0186
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a Low-Cost Silicone and Water-Based Soft Actuator with a High Load-to-Weight Ratio

Abstract: Traditional actuators, such as motors as well as hydraulic or pneumatic artificial muscles, demonstrate excessive noise, a heavy weight, and a large size, which limit their practical application in many areas. Therefore, for many decades, scientists have worked to develop new types of silent, small, and light actuators. In this article, a novel soft actuator (actuator 3 ) with a high load-to-weight ratio from silicone and a low-boiling liquid (ethanol: actuator 3E or water: actuator 3W ) is presented and is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Cheng et al proposed a manipulator based on SMA actuators that has nine degrees of freedom and closed-loop control that employs gyroscope and accelerometer modules [ 60 ] or manipulators driven by SMA coils and Hall sensors [ 61 ]. Li et al proposed an SMA-driven manipulator position control method based on fuzzy delay algorithms to increase manipulator accuracy due to the nonlinear hysteretic behavior of SMAs [ 62 ]. Jizhuang et al approached the control of the frog robot through an open-loop control system that connected an HC-12 module to the robot microcontroller, which allowed the robot to be controlled from a PC.…”
Section: State Of the Art In Soft Roboticsmentioning
confidence: 99%
“…Cheng et al proposed a manipulator based on SMA actuators that has nine degrees of freedom and closed-loop control that employs gyroscope and accelerometer modules [ 60 ] or manipulators driven by SMA coils and Hall sensors [ 61 ]. Li et al proposed an SMA-driven manipulator position control method based on fuzzy delay algorithms to increase manipulator accuracy due to the nonlinear hysteretic behavior of SMAs [ 62 ]. Jizhuang et al approached the control of the frog robot through an open-loop control system that connected an HC-12 module to the robot microcontroller, which allowed the robot to be controlled from a PC.…”
Section: State Of the Art In Soft Roboticsmentioning
confidence: 99%
“…As PCMEC actuators, these designs allow remote actuation to avoid the need of a pressure source, but remain subject to leaks. Ethanol Han et al (2019) , Chellattoan et al (2020) , Kang et al (2070) , water Li J. et al (2020) , FC-72 (3M™ Fluorinert™ Electronic Liquid FC-72) Matsuoka et al (2016) , acetone Chellattoan et al (2020) , or Novec ( Boyvat et al, 2019 ; Narumi et al, 2020 ; Ueno and Monnai, 2020 ) was reported.…”
Section: Influence Of the Phase-change Fluidmentioning
confidence: 99%
“…Several functional structures have been build using PCMECs, from simple bilayer Miriyev et al (2018a) , Li J. et al (2020) to piston-like Miriyev et al (2017) , Miriyev et al (2018b) and McKibben-like Miriyev et al (2017) , Bilodeau (2018) artificial muscles. Other original designs have been demonstrated to build PCMEC actuators capable of locomotion ( Li X. et al, 2020 ; Noguchi and Tsumori, 2020 ).…”
Section: Toward Pcmec Functionalization: a Voxel-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent actuators use entrained liquid vesicles or films to form an expanded cavity for actuation [ 30 , 31 ]. Electrically triggered deformation of soft elastic films using liquid-gas conversion of liquids has been reported to exhibit large area expansion [ 32 ]. Aslan and colleagues reported ethanol-gas phase transition composites with 900% expansion and correspondingly high stress (up to 1.3 MPa) and low density (0.84 g/cm 3 ).…”
Section: Introductionmentioning
confidence: 99%